2000
DOI: 10.2134/agronj2000.925902x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Statistical Models Describing Potato Yield Response to Nitrogen Fertilizer

Abstract: Estimation of optimum fertilizer rates is of interest because of growing economic and environmental concerns. Optimum fertilizer rates can be determined by fitting statistical models to yield data collected from N fertilizer experiments. We evaluated quadratic, exponential, and square root models describing the yield response of potato (Solanum tuberosum L.) to six rates of N fertilization (0–250 kg N ha−1) with and without supplemental irrigation at four on‐farm sites in each of three years (1995 to 1997) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
62
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 7 publications
12
62
0
2
Order By: Relevance
“…The Nop averaged over all sites was 175 kg N ha -1 (Bélanger et al 2000b), which is similar to the current general recommendation for N fertilization in Atlantic Canada (Bernard et al 1993). The Nop, however, varied greatly among sites (105 to 250 kg N ha -1 ).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The Nop averaged over all sites was 175 kg N ha -1 (Bélanger et al 2000b), which is similar to the current general recommendation for N fertilization in Atlantic Canada (Bernard et al 1993). The Nop, however, varied greatly among sites (105 to 250 kg N ha -1 ).…”
Section: Resultssupporting
confidence: 83%
“…In our study, the spring soil NO 3 -N content and Nop had a wide range, as reported previously (Bélanger et al 2000b). Therefore, the Nop and the range of soil NO 3 -N content should have been adequate to establish a satisfactory relationship.…”
Section: Soil No 3 -N Contents In Spring and Mid-seasonsupporting
confidence: 88%
See 1 more Smart Citation
“…No Brasil, é possível encontrar recomendações de fertilização variando de 60 a 250 kg ha -1 de N (Fontes, 1999); a dose ótima a ser fornecida depende de vários fatores, como produtividade esperada, pluviosidade, cultura anterior, práticas culturais, entre outros (Fontes, 2001). Além disso, a dose a ser aplicada deve otimizar o rendimento da cultura e a qualidade final do produto, maximizar a rentabilidade e reduzir os riscos de contaminação ambiental (Bélanger et al, 2000).…”
Section: Introductionunclassified
“…A partir da equação ajustada para a produtividade comercial, em cada condição de disponibilidade de P no solo, foi calculada a dose de máxima eficiência econômica (DMEE), ou seja, a dose de P 2 O 5 (kg/ha) em que R$ 1,00 de P 2 O 5 adicional retornaria R$ 1,00 de batata produzida. A DMEE foi calculada igualando-se a derivada primeira de cada equação com a relação de preços do fertilizante fosfatado e da batata (Fontes et al, 1997;Bélanger et al, 2000). A relação de preços foi calculada considerando o preço médio (R$ 0,94/ kg) da batata comercializada em São Paulo durante o ano de 2011 (CEPEA/ ESALQ/USP, 2012) e o preço do P 2 O 5 do superfosfato triplo (R$ 4,46/kg).…”
Section: Methodsunclassified